Pengaruh Corporate Governance, Rasio Keuangan, Ukuran Perusahaan dan Makroekonomi Terhadap Financial Distress (Studi pada Perusahaan Sektor Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahu 2012-2016) - KURNIASANTI, ALFIAH; MUSDHOLIFAH (Jurnal Ilmu Manajemen (JIM), 2018)
Financial distress that happens continuously will make the company went bankrupt. This study aims to determine the factors that affect the financial distress companies in the Indonesian mining sector. This study uses corporate governance (board of commissioners, managerial ownership, institutional ownership, audit committee, and independent commissioner, financial ratios (profitability, leverage, liquidity and efficiency), firm size (Ln total assets) and macroeconomic (inflation and interest rate) to predict the companys financial distress condition. The sample of this research is 17 Indonesian mining sector companies selected using purposive sampling. This study uses data in the period 2012-2016. Data analysis technique used is logistic regression. The results show that profitability (return on assets) and efficiency (asset turnover) negatively affect on financial distress and other variables of board of commissioners, managerial ownership, institutional ownership, audit committee, independent commissioner, leverage, liquidity, firm size, inflation and interest does not affect on financial distress. Therefore, the mining sector companies are expected to pay attention to increase the value of return on assets and asset turnover so that companies can avoid financial distress. Keywords: financial distress, corporate governance, financial ratio, firm size, macroeconomic.